Strengthening innovative behavior: the role of supportive climate and absorptive capacity - Rozak, Hasan; Taswan, Taswan; Mansyur, Anwar; Fachrunnisa, Olivia (Business: Theory and Practice, 2024)
This study explores how to achieve innovative behavior in Indonesian SMEs in the culinary and craft sectors. We conducted a literature review and collected data from 372 SME owners. Using SEM analysis, we found that a supportive climate positively impacts both potential and realized absorptive capacity, which in turn positively impacts innovative behavior. The study’s findings contribute to social exchange theory and have implications for SME sector organizations. Limitations include the data collection method, sample size and selection, research objective, cross-sectional design, and self-reported data. Future research could address these limitations and investigate other organizational factors that may influence innovative behavior in SMEs.